Impact of electrical intertie capacity on carbon policy effectiveness. (February 2017) - English, J.; Niet, T.; Lyseng, B.; Palmer-Wilson, K.; Keller, V.; Moazzen, I.; Pitt, L.; Wild, P.; Rowe, A.
Abstract: This study investigates the potential cost and emissions reductions that result from an increase in electricity transmission capacity between Canada's two westernmost provinces: Alberta, a fossil fuel dominated jurisdiction, and British Columbia, a predominantly hydroelectric jurisdiction. A bottom-up model is used to find the least cost electricity generation mix in Alberta and British Columbia under different carbon policies. The long-term evolution of the electricity system is determined by minimizing net present cost of electricity generation for the time span of 2010–2060. Different levels of intertie capacity expansion are considered together with a variety of carbon tax and carbon cap scenarios. Results indicate that increased intertie capacity reduces the cost of electricity and emissions under carbon pricing policies. However, the expandable intertie does not encourage greater adoption of variable renewable generation. Instead, it is used to move low-cost energy from the United States to Alberta. The optimal intertie capacity and cost reduction of increased interconnectivity increases with more restrictive carbon policies. Highlights: A techno-economic optimization model is used to examine electricity generation in western Canada. Interprovincial electricity transmission can decrease carbon abatement costs. Market conditions can reduce the expected synergy between storage hydroelectricity and variable renewable generation. Inconsistent carbon policies between regions mean emissions are moved, not avoided.